COVID-19-Associated Fungal Infections: An Urgent Need for Alternative Therapeutic Approach? - Domán, Marianna; Bányai, Krisztián (Frontiers in Microbiology, 2022)
Secondary fungal infections may complicate the clinical course of patients affected by viral respiratory diseases, especially those admitted to intensive care unit. Hospitalized COVID-19 patients are at increased risk of fungal co-infections exacerbating the prognosis of disease due to misdiagnosis that often result in treatment failure and high mortality rate. COVID-19-associated fungal infections caused by predominantly Aspergillus and Candida species, and fungi of the order Mucorales have been reported from several countries to become significant challenge for healthcare system. Early diagnosis and adequate antifungal therapy is essential to improve clinical outcomes, however, drug resistance shows a rising trend highlighting the need for alternative therapeutic agents. The purpose of this review is to summarise the current knowledge on COVID-19-associated mycoses, treatment strategies and the most recent advancements in antifungal drug development focusing on peptides with antifungal activity.